Plunging Brno into darkness: Measuring the contribution of public lighting to the total luminance of the night sky - Novák, F.; Baxant, P. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
The article deals with the description of measurements of night sky luminance in urban agglomeration with emphasis on the determination of changes in the values of these luminances when public and architectural lighting is temporarily turned off. The measurements took place in Brno, the second largest city in Czech Republic, with the population around 382 thousand. The presented paper is one of the perspectives on the impact of human activity on the surrounding environment and an example of a possible solution to quantify the impact of the introduction of technologies that directly or indirectly affect the environment not only for humans, but also for almost all forms of life.
Keywords: ALAN; artificial light at night; luminance measurement; light pollution; public lighting; luminance analyzer; intrusive light; LumiDISP; astronomy